Identification of Biophilic Patterns in the Vernacular Architecture of Kampung Naga - Ayu Lestari, Tidi (RUAS, 2025)
Biophilic design is an applied approach rooted in historical understanding and human intuition toward nature, supported by scientific findings that affirm the importance of human-nature relationships for physical, psychological, and emotional well-being. This understanding aligns with the philosophy of the Sundanese people—particularly the community of Naga Village—who maintain a strong connection with nature. Naga Village was chosen as the case study for its ability to preserve the integration of culture, architecture, and ecology amid modernizing pressures. This paper aims to identify 14 biophilic patterns in the vernacular architectural concept of Naga Village across three spatial contexts: macro (ecology), meso (settlement patterns), and micro (architecture). The method employed is qualitative-comparative, using thematic visual analysis through a matrix that matches biophilic patterns with the three spatial contexts of Naga Village. The results indicate a direct correlation between biophilic principles and the ecological, settlement, and architectural elements that have evolved through generations in Naga Village.